Communicating climate-change impacts to youth: a social influence theory perspective - Cannon, Lauren (Kansas State University, 2024)
Climate change is known to have severe impacts on Earth’s temperature, organisms, human health, and habitats. Despite overwhelming scientific evidence, many individuals hold misbeliefs about climate change. Misbeliefs can prevent policy changes or environmental action to reduce climate-change impacts from taking place. Previous scholars have addressed the potential causes behind these misbeliefs, including misinformation, confirmation bias, and tribalism. Since current solutions have not yet significantly reduced these misbeliefs or their causes, this report explores the issue using a social influence theory perspective. By synthesizing literature on social influence theory, climate-change communication, and the use of youth groups and activities for education, it is concluded that communicating to youth groups and their leaders about climate-change impacts could produce the greatest change in reducing misbeliefs. This is due to the combination of normative social influence, leadership and mentorship influence, and healthy environments in youth group structures. These findings inform a communication plan for reducing misbeliefs about climate in youth groups in low socioeconomic areas of Kansas. By educating youth about climate change, we can significantly reduce misbeliefs overall through generational replacement and allow more policy changes and environmental actions to be implemented to reduce climate-change impacts.
Keywords: Climate change communication; Social influence theory; Youth group education